LONGITUDINAL STUDY: CHANGES IN RELIGIOUS PATTERNS OF ISLAMIC RELIGIOUS EDUCATION STUDENTS DURING THE STUDY PERIOD - Fikri, Ahmad; Mahyuzar, Mahyuzar; Sururuddin, Sururuddin; Fahri, Ismail (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to analyze changes in the religiosity patterns of students of the Islamic Religious Education (PAI) Study Program during the study period using a longitudinal quantitative approach. The research sample consisted of 180 6th semester students from a total of 210 students at the Sultan Thaha Saifudin Jambi State Islamic University. Data were collected through a religiosity questionnaire based on the five dimensions of religiosity according to Glock and Stark, analyzed descriptively and inferentially. The results showed a significant decrease in the dimensions of worship practices and ideology, and an increase in the dimension of religious knowledge. Social and academic environmental factors also influence the dynamics of student religiosity. These findings provide important input for the development of religiosity development in Islamic higher education environments